Pengaruh Komunikasi, Pelatihan Dan Kompetensi Terhadap Kinerja Karyawan Pada PT. Matahari Departemen Store Thamrin Plaza Medan - Iman Enuar Halawa; Marni Irawaty Manalu; Siti Syfa Meutia; Maya Agustina Tanjung (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
PT. Matahari Department Store is a company engaged in retail. This study aims to determine and analyze the effect of communication, training, and competence on employee performance. The research method uses quantitative. And the sampling technique used is random sampling. Based on the results, it is stated that communication, training, and competence simultaneously or partially have a positive and significant influence on employee performance. Where the value of Ajusted R Square is 0.693, this means that 69.3% of the variation in employee performance variables can be explained by variations in the communication, training, competence variables while the remaining 30.7% is influenced by other variables that cannot be explained in this study